Pengembangan Tempe Fantasy dengan Penambahan Pewarna Alami dan Rempah-Rempah Mengandung Antioksidan - Sulistyo, Joko; Dewi, Irra Chrisyanti; Oktavio, Adrie (Abdimas Indonesian Journal, 2024)
Color is one of the most relevant organoleptic attributes that directly influence consumer acceptance and food selection. Natural dyes play an important role in the food industry, not only because of their aesthetic appeal but also their health benefits. Natural dyes offer a variety of health-promoting properties, such as antioxidant, antimicrobial, and anti-inflammatory effects. Therefore, this important characteristic is the reason for adding coloring to develop a tempeh product namely Tempeh Fantasy. This research aims to determine the functional properties, enamelyspecially the antioxidant activity of tempeh products that have been added with natural colorings and aromatic ingredients. Through community service activities, research, and training, the development of tempeh-fantasy innovation has been carried out, which involves soaking cooked soybeans in combination solutions of butterfly pea flower and star anise powder, roselle flower and cinnamon, moringa leaf extract and ginger powder, turmeric and garlic extract, as well as Pangium nut and black garlic solution, then adding tempeh starter and further fermenting it. The results showed that the addition of natural colorings and herb-spices to tempeh succeeded in increasing its antioxidant activity. Additionally, the addition of natural colorings and spices to tempeh can enhance its exotic color and attractive aroma.